Convergence of blockchain technology and E-business : concepts, applications, and case studies - Sumathi, D. (Boca Raton : CRC Press, 2021)
"The purpose of this edited book is to provide the relevant technologies and case studies in a concise format that will simplify and streamline the processing of blockchain. The goal is for the contents of this book to change the way business transformations are conducting in economic and social systems. The book examines blockchain technology, the transaction attributes, and its footprint in various fields. It offers fundamentals and terminologies used in blockchain, architecture, and various consensus mechanisms that can be deployed in areas such as healthcare, smart cities, and supply chain management. The book provides a widespread knowledge into the deployment of security countermeasures that can be implemented for a blockchain network and enables the reader to consider the management of business processes and the implementation process in detail. The book highlights the challenges and provides various e-business case studies of security countermeasures. The book serves researchers and businesses by providing a thorough understanding of the transformation process using blockchain technology"--
Blockchain and bitcoin scripts / S. Prithi, Prabha Selvaraj, S. Suganthi, D. Sumathi.
OCLC-licensed vendor bibliographic record.
Keywords: Business -- Data processing; Electronic commerce; Blockchains (Databases) -- Industrial applications; COMPUTERS / Machine Theory; COMPUTERS / Cryptography; TECHNOLOGY / Engineering / General